In situ synthesis of graphene-encapsulated gold nanoparticle hybrid electrodes for non-enzymatic glucose sensing. (March 2016) - Thanh, Tran Duy; Balamurugan, Jayaraman; Hwang, Jun Yeon; Kim, Nam Hoon; Lee, Joong Hee
Abstract: A novel route for in-situ synthesis of high-quality gold nanoparticles-encapsulated few layered graphene (AuNP-FLG) nanohybrids has been established. The AuNP-FLG nanohybrids were successfully synthesized by chemical vapor deposition technique and used as an electrocatalyst for high sensitive non-enzymatic glucose sensors. The amperometric response of the AuNP-FLG based electrode achieved an excellent electrocatalytic activity towards glucose oxidation with a wide linear detection range of 6 μM–28.5 mM, low detection limit of 1 μM and a sensitivity of 0.195 μA mM −1 cm −2 at operating potential of 0.0 V. Furthermore, the electrode also showed long-term stability (retention of 95.4% after two week) with negligible interference from ascorbic acid, 4-acetamidophenol and uric acid. The results implied that AuNP-FLG could be a promising electrode material in the development of non-enzymatic glucose sensors.